Penerapan Teori Asal Usul Kepemimpinan dalam Institusi Pendidikan Islam - Apriyenti, Apriyenti; Oktawira, Leni; Khaidir, Asmendri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to find out the application of the origin of leadership in Islamic Education institutions. This study uses the literature study method as the main research approach. The data is collected through systematic searches in physical and digital libraries, by utilizing academic databases such as Google Scholar and national journal portals. Literature selection criteria include relevance to the topic, academic credibility, and up-to-date publications. Data were analyzed using a descriptive qualitative approach. The results of the analysis show that leadership is the process of influencing or freeing a leader through his followers in achieving organizational goals and having the ability to carry them out so that he becomes a competent leader. Becoming a successful leader is certainly not easy, there are a lot of problems that arise when becoming a leader, one of the factors that support the success of one's leadership is by studying leadership theory. These theories are genetic leadership theory, social leadership theory, and ecological leadership theory. The importance of studying this theory implies that a leader can understand the extent of his abilities, what competencies have been learned and what learning process he has done and learn the origin of the leadership he masters which can then be used as a reflection of himself to run an organization or institution more neatly arranged in accordance with very good achievement targets.